IDENTITAS KRISTIANI DALAM PLURALISME BUDAYA MELALUI PENDEKATAN KONTEKSTUAL - Juwita Pandung; Jimmy Joys Juna; Lispa Matasak; Palentina Ko'bong; Risma Talo (Adisam Publisher, 2025)
This paper explores the role of contextual theology in bridging Christian faith with local culture, particularly within culturally diverse societies such as Indonesia. Acknowledging that the Gospel is proclaimed and lived out in various cultural settings, contextual theology emerges as an approach that seeks to ensure the message of the Gospel remains relevant, understandable, and authentically experienced in the life of believers. Through a literature review, this paper outlines the key principles of contextualization, such as inculturation, relevance, and faithfulness to the Gospel and presents various examples of its application in church life and Christian witness. The findings suggest that contextualization, when carried out reflectively and responsibly, can strengthen the identity of Christian faith while broadening the scope of its witness in pluralistic societies. Contextual theology is not a compromise of the Gospel, but a way of living out its truth in a more grounded and impactful manner.